2009
DOI: 10.1007/s10661-009-0822-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sampling effort and sampling frequency on the composition of the planktonic crustacean assemblage: a case study of the river Danube

Abstract: Although numerous studies have focused on the seasonal dynamics of riverine zooplankton, little is known about its short-term variation. In order to examine the effects of sampling frequency and sampling effort, microcrustacean samples were collected at daily intervals between 13 June and 21 July of 2007 in a parapotamal side arm of the river Danube, Hungary. Samples were also taken at biweekly intervals from November 2006 to May 2008. After presenting the community dynamics, the effect of sampling effort was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Vadadi‐Fülöp et al . () reported marked short‐term variations over weekly timescales in the abundance and diversity of planktonic crustaceans in the Danube River, suggesting that temporal variation can be high and frequent sampling may be required to represent site conditions. Zooplankton abundances tend to be less variable in main channel habitats compared with backwaters (Burdis and Hoxmeier, ), and Dickerson et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vadadi‐Fülöp et al . () reported marked short‐term variations over weekly timescales in the abundance and diversity of planktonic crustaceans in the Danube River, suggesting that temporal variation can be high and frequent sampling may be required to represent site conditions. Zooplankton abundances tend to be less variable in main channel habitats compared with backwaters (Burdis and Hoxmeier, ), and Dickerson et al .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, plankton groups showed variable responses to local habitat conditions and reach-scale differences in water quality. Vadadi-Fülöp et al (2010) reported marked short-term variations over weekly timescales in the abundance and diversity of planktonic crustaceans in the Danube River, suggesting that temporal variation can be high and frequent sampling may be required to represent site conditions. Zooplankton abundances tend to be less variable in main channel habitats compared with backwaters (Burdis andHoxmeier, 2011), andDickerson et al (2010) concluded that hydrology must be accounted for before zooplankton can be used as indicators of environmental stress because they respond to flow characteristics as well as local environmental conditions such as water temperature.…”
Section: Relevance To Biomonitoringmentioning
confidence: 99%
“…Much of the selected papers derived their findings from samples collected at weekly and fortnightly intervals at least during the growing season, which is a common and recognised method in limnology, although significant variation in community dynamics of zooplankton may remain hidden at fortnightly sampling (Vadadi-Fülöp et al, 2010).…”
Section: Temporal Settingmentioning
confidence: 99%